An Evaluation of Credit Rating Agencies, Credit Ratings, and Credit Default Swaps - DAYI, Faruk; TANTOUN, Ashraf (Burdur Mehmet Akif Ersoy University, 2023)
Investors face different risks in international markets than in national ones. Effective risk management can help protect investors from these risks in global markets. Various indicators and financial instruments are utilized in risk management. Credit rating agencies assess the risk level of institutions or organizations in global markets and provide information to global investors. Credit rating agencies evaluate institutions or organizations by assigning credit ratings. Credit default swaps (CDS) have recently become popular hedging instruments. Credit ratings and CDS premiums are essential sources of data used to assess the risk of an institution or organization. Credit ratings indicate the investment grade of countries. CDS premiums are contracts entered into by creditors to protect themselves in the event of a borrower's default. It is argued that sovereign credit ratings and CDS premiums were misleading during the 2008 economic crisis, after which the reliability and validity of credit ratings and CDS premiums became a subject of debate. This study examined the relationship between credit ratings and CDS premiums and assessed the functionality of the system on critics.
Keywords: 1. No poverty